A Scan and Pay Mobile Application for Grocery Store: Development and Implementation - Chow Yuk Leong; Suhaimi Abd Ishak (Applied Information Technology And Computer Science, 2023)
This project aims to enhance the customer experience in grocery shopping by developing a mobile application called Scan and Pay for Bistari Mini Market. The current manual pricing and payment processes in the mini market bring to challenges such as missing price tags, long queues, and customer dissatisfaction. The Scan and Pay mobile application allow customers to scan item barcodes using their smartphones, providing accurate and real-time information on prices, names, and discounts. Customers can add items to their shopping carts, view comprehensive details, and choose their preferred payment method. The expected outcome includes a user-friendly application for customers and administrators, offering convenience and reduced waiting times. This project revolutionizes grocery shopping by leveraging technology to streamline processes, improve satisfaction, and promote efficiency in the mini market industry.